Environmental Health Tracking Improves Pesticide Use Data to Enable Research and Inform Public Health Actions in California. (September 2017) - Richardson, Maxwell J.; Madrigal, Daniel S.; Wilkie, Alexa; Wong, Michelle; Roberts, Eric
Abstract : Pesticides have adverse impacts on the environment and public health. In response to growing public concern over these impacts, California implemented the Pesticide Use Reporting (PUR) program in 1990. The PUR program is widely recognized as the world's most comprehensive pesticide reporting system, and its pesticide application records are highly detailed. However, the complexity and volume of PUR data require a level of data skills and resources beyond many government agencies, public health professionals, and community stakeholders. Over the past decade, the California Environmental Health Tracking Program has undertaken multiple strategies to make PUR data more accessible, understandable, and useful to a diversity of data users. Three specific efforts are described in detail—the Pesticide Linkage Service, the Pesticide Mapping Tool, and a policy-relevant analysis on pesticide use near schools—as are their impacts on environmental and public health research, community outreach and education, and policy change.